Flexible copper foil substrate
By forming a nickel-copper alloy layer on the flexible copper foil substrate, the structural problems caused by the nickel-layer oxidation corrosion during the nickel-immersion process are solved, and the effect of resistance to electrochemical corrosion and sufficient peel strength is achieved.
Patent Information
- Application Number
- CN202311759836.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-07
- Filing Date
- 2023-12-18
- Publication Date
- 2025-05-09
AI Technical Summary
The well-known flexible copper foil substrate is prone to separation of the copper layer from the polyimide substrate during the nickel-imide gold immersion process due to oxidation and corrosion of the nickel layer, which damages the structure of the flexible circuit board.
The nickel-copper alloy layer is formed by electroless plating, which contains nickel, copper and phosphorus. The copper content is greater than 30% by weight, less than 80% by weight, and the phosphorus content is less than 5% by weight, so as to increase the corrosion potential of the nickel-copper alloy layer in the sulfuric acid solution.
It is resistant to electrochemical corrosion and maintains sufficient peel strength to ensure the structural stability of the flexible copper foil substrate during nickel-immersion gold-immersion process.
Smart Images

Figure CN119967706A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flexible copper foil substrate, in particular to a flexible copper foil substrate resistant to electrochemical corrosion. Background Art
[0002] Flexible copper foil laminate (FCCL) is generally manufactured by a wet metal process, in which a nickel layer is formed on the surface of a polyimide substrate and a copper layer is electroplated on the nickel layer.
[0003] By forming a nickel layer between the copper layer and the polyimide substrate, the peeling strength between the metal conductive layer formed by the nickel layer and the copper layer and the polyimide substrate can be increased, thereby improving the structural strength of the flexible copper foil substrate.
[0004] However, when the conventional flexible copper foil substrate is manufactured into a flexible printed circuit board (FPC) and subsequently subjected to electroless nickel immersion gold (ENIG), the reduction potential of metallic nickel (-0.25V) is lower than the reduction potential of metallic copper (+0.34V). Therefore, when reducing gold ions during the electroless nickel immersion gold process, metallic nickel is prone to lose electrons, thereby causing oxidative corrosion of the nickel layer, also known as electrochemical corrosion.
[0005] Then, if the nickel layer is oxidized and corroded, the metal circuit on the copper layer may be separated from the polyimide substrate, thereby destroying the structure of the flexible circuit board.
[0006] Therefore, in the technical field of the present invention, there is room for further improvement in flexible copper foil substrates having an electrochemical corrosion resistance effect. Summary of the invention
[0007] The inventors have found that the nickel-copper alloy layer of the present invention will not be corroded due to loss of electrons in an acidic gold plating solution, and will not affect the etching of the manufacturing circuit. In other words, by using a chemical plating method and a specific composition of the nickel-copper alloy layer, the corrosion potential of the nickel-copper alloy layer in a sulfuric acid solution can be increased, and a flexible copper foil substrate with electrochemical corrosion resistance and sufficient peeling strength can be obtained.
[0008] In order to solve the above problems, the present invention provides a flexible copper foil substrate, which comprises: a polyimide substrate; a nickel-copper alloy layer, which is formed on at least one side of the polyimide substrate by chemical plating, the nickel-copper alloy layer comprises nickel, copper and phosphorus, and the content of the copper is greater than 30wt% of the nickel-copper alloy layer, the content of the phosphorus is less than 5wt% of the nickel-copper alloy layer, and the nickel-copper alloy layer has a surface area of 0.02v oThe corrosion potential in a 1% sulfuric acid solution is greater than -20mV; the copper layer is formed on the side of the nickel-copper alloy layer away from the polyimide substrate and is composited with the nickel-copper alloy layer to form a metal conductive layer.
[0009] In an embodiment, the copper content is less than 80 wt % of the nickel-copper alloy layer.
[0010] In an embodiment, the nickel-copper alloy layer is a single plated layer.
[0011] In an embodiment, the nickel-copper alloy layer further includes at least one selected from the group consisting of iron, cobalt, molybdenum, tungsten, tin, chromium, and zinc.
[0012] In an embodiment, the copper layer is formed on the nickel-copper alloy layer by electroplating, and the copper layer has a thickness of 0.2-20 μm.
[0013] In an embodiment, the peel strength between the metal conductive layer and the polyimide substrate is ≥ 0.7 kgf / cm.
[0014] The present invention has been made in view of the above-mentioned known problems, and an object of the present invention is to provide a flexible copper foil substrate which is resistant to electrochemical corrosion and has sufficient peel strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 FIG. 4 is a schematic cross-sectional view of a flexible copper foil substrate according to an embodiment of the present invention.
[0016] Figure 2 It is a production flow chart of a flexible copper foil substrate according to an embodiment of the present invention.
[0017] Figure 3 The manufacturing process of the flexible printed circuit (FPC) of the present invention is shown.
[0018] Figure 4 (a) is a photograph of the appearance of the etching circuit of Comparative Example 5 of the present invention; Figure 4 (b) is a photograph of the appearance of the etched circuit of Example 1 of the present invention.
[0019] Figure 5 (a) is a photograph of the ENIG-treated comparative example 1 of the present invention; Figure 5 (b) is a photograph after ENIG of Example 1 of the present invention.
[0020] Figure 6 (a) is a photo of the sample after etching of Example 4 of the present invention; Figure 6 (b) is a photo of the sample after etching of Example 1 of the present invention; Figure 6 (c) is a photograph of the sample after etching of Comparative Example 5 of the present invention.
[0021] [Reference Signs]
[0022] 1 Polyimide substrate
[0023] 11 First Surface
[0024] 12 Second Surface
[0025] 2 Nickel-copper alloy layer
[0026] 3 Copper Layer
[0027] 4 Gold Layer
[0028] 100 Flexible copper foil substrate
[0029] 900 Flexible Circuit Board. DETAILED DESCRIPTION
[0030] The following describes the implementation scheme of the present invention through specific specific examples, and those skilled in the art can understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0031] Unless otherwise specified herein, the term "AB" used in the specification and the appended claims includes the meaning of "A or more and B or less". For example, the term "10-40% by weight" includes the meaning of "10% by weight or more and 40% by weight or less".
[0032] Flexible copper foil substrate
[0033] First, please refer to Figure 1 , Figure 1 FIG. 1 is a schematic cross-sectional view of a flexible copper foil substrate 100 according to an embodiment of the present invention. Figure 1 As shown, a flexible copper foil substrate 100 according to an embodiment of the present invention comprises: a polyimide substrate 1; a nickel-copper alloy layer 2; and a copper layer 3. The polyimide substrate 1 comprises a first surface 11 and a second surface 12, and the nickel-copper alloy layer 2 and the copper layer 3 can be combined into a metal conductive layer.
[0034] Then, if Figure 1 As shown, the nickel-copper alloy layer 2 is formed on the first surface 11 of the polyimide substrate 1, and the copper layer 3 is formed on the side of the nickel-copper alloy layer 2 away from the polyimide substrate 1, that is, the structure of the flexible copper foil substrate 100 is sequentially the polyimide substrate 1, the nickel-copper alloy layer 2 and the copper layer 3. In addition, the nickel-copper alloy layer 2 can also be formed on the first surface 11 and the second surface 12 of the polyimide substrate 1 at the same time. Next, the flexible copper foil substrate 100 of the present invention is described in detail.
[0035] Polyimide substrate
[0036] The polyimide substrate is a sheet / film substrate formed of polyimide (PI), and its thickness can be about 5-150 μm, and there is no particular limitation. In addition, the polyimide substrate can also be made of transparent polyimide, such as polyimide with a light transmittance greater than 87%. In addition, the polyimide substrate can be a commercially available product, such as a polyimide film made by Damai Technology, model TX6-025.
[0037] Nickel copper alloy layer
[0038] The nickel-copper alloy layer includes nickel, copper and phosphorus. Specifically, by including sodium hypophosphite as a reducing agent in the chemical plating solution, phosphorus will also be precipitated as one of the alloy components during the reduction deposition process of nickel ions. In the present invention, the phosphorus content is less than 5wt% of the nickel-copper alloy layer and can be controlled by the composition and operating conditions of the chemical plating solution. This is because if the phosphorus content is above 5wt% of the nickel-copper alloy layer, there will be obvious metal residues under the etching solution of H2O2 / H2SO4, resulting in the problem of increased line width when the subsequent ENIG of the circuit is performed.
[0039] Next, in the nickel-copper alloy layer of the present invention, the copper content is greater than 30wt% of the nickel-copper alloy layer. This is because the reduction potential of metal copper is greater than the reduction potential of metal nickel. Therefore, by including a specific proportion of copper in the nickel-copper alloy layer, it is possible to reduce the situation where metal nickel loses electrons and is oxidized and corroded during ENIG. In addition, if the copper content is less than 30wt% of the nickel-copper alloy layer, the nickel-copper alloy layer is 0.02v o The corrosion potential in a 1% sulfuric acid solution may be less than -20mV, which cannot achieve the effect of electrochemical corrosion resistance.
[0040] Then, the inventors found that if the copper content is greater than 80wt% of the nickel-copper alloy layer, the peel strength between the metal conductive layer and the polyimide substrate will be significantly reduced, which may reduce the structural strength of the FCCL. Therefore, the copper content is preferably greater than 30wt% and less than 80wt% of the nickel-copper alloy layer, and the copper content is more preferably 40wt%-60wt% of the nickel-copper alloy layer.
[0041] On the other hand, the nickel-copper alloy layer includes, in addition to nickel, copper and phosphorus, any metal that can be co-plated with nickel can be appropriately added according to the desired characteristics, and there is no particular limitation. Specifically, the nickel-copper alloy layer of the present invention may also include at least one selected from the group consisting of iron, cobalt, molybdenum, tungsten, tin, chromium and zinc. In addition, the total thickness of the double-sided metallized nickel-copper alloy layer may be 100-250nm, preferably 160-200nm. On the other hand, the thickness of the single-sided metallized nickel-copper alloy layer is preferably 80-100nm.
[0042] Here, the thickness of the nickel-copper alloy layer can be measured using an X-ray film thickness meter (purchased from General Technology Company, model Specifically, a 10cm*10cm coating sample is placed on the measuring table to measure the total thickness of the nickel-copper alloy layer.
[0043] In addition, the nickel-copper alloy layer of the present invention can be a single plating layer, that is, it can achieve the effect of electrochemical corrosion resistance without being combined with other layers, thereby saving production costs.
[0044] Next, in the present invention, the nickel-copper alloy layer is formed on at least one side of the polyimide substrate by chemical plating. As for chemical plating, it can be a known chemical plating method (a method of reducing metal ions to metals in a solution containing metal ions using a strong reducing agent and depositing them on the surface of various materials to form a dense coating according to the principle of redox reaction), and is not particularly limited. Again, as for a specific example of chemical plating, firstly, a rolled polyimide substrate (purchased from Damai Technology, model TX6-025) is subjected to continuous hydrophilic modification treatment on a corona treatment machine (Corona treatment machine, purchased from WEDGE, Japan), and the operating conditions are power 3kw and speed 3m / minute.
[0045] Next, the hydrophilized polyimide substrate was cut into a size of 20cm*20cm and immersed in a 2wt% KOH solution at 40°C for 150 seconds. Then, the catalyst was applied according to the SLP metallization process (SLPprocess) of Okuno Pharmaceutical Co., Ltd. of Japan, and the SLP series of electroless nickel plating reagents (including SLP-200, SLP-300, SLP-400, SLP-500) were used to sequentially perform charge adjustment, pre-immersion, catalysis, and acceleration steps. The operating conditions are described as follows.
[0046] 1. Soak the hydrophilized polyimide substrate in a 65°C SLP-200 solution for 75 seconds for charge adjustment, remove and rinse with water. 2. Continuously soak in a 25°C SLP-300 solution for 25 seconds and a SLP-400 solution for 75 seconds to allow the catalyst to adhere to the surface of the polyimide substrate, remove and rinse with water. 3. Then soak in a 35°C SLP-500 solution for 75 seconds to activate the catalyst, remove and rinse with water to form a polyimide substrate with a palladium catalyst on one or both sides. Then, the above-mentioned chemical plating treatment is performed on the polyimide substrate with a palladium catalyst to form a nickel-copper alloy layer; wherein the palladium catalyst comes from the above-mentioned SLP series electroless nickel plating reagent.
[0047] Copper Layer
[0048] The copper layer of the present invention is not particularly limited, as long as it can form a copper layer for subsequent etching circuits. In one embodiment of the present invention, the copper layer is preferably plated on the nickel-copper alloy layer by electroplating. The electroplating solution that can be used for the copper layer can be a commercial product, such as copper sulfate electroplating solution (purchased from Jiwei Industrial Co., Ltd.). In addition, the thickness of the copper layer is preferably 0.2-20 μm.
[0049] Specifically, the electroplating copper layer can be carried out in the following manner: fix the polyimide substrate plated with the nickel-copper alloy layer with a stainless steel frame, soak it in a 3 vol% H2SO4 solution for 1 minute to clean the surface, and then put it into an electroplating tank (for example, a 20L small electroplating copper tank purchased from Xuanheng Enterprise Co., Ltd.) for copper plating, and the electroplating area is 15cm*15cm. The electroplating solution contains 150g / L H2SO4, 120g / L CuSO4 and 50ppm chloride ions, and can further contain appropriate amounts of gloss agent and flattening agent as needed. In addition, the power-on conditions of electroplating are 6A current, 3V voltage, and 2 minutes. Take it out for water washing and drying, and you can get a single-sided or double-sided electroplated copper layer with a copper thickness of about 1μm.
[0050] Here, the thickness of the copper layer can be measured using a copper thickness measuring instrument (purchased from Xinshen Co., Ltd.). Specifically, a 10 cm*10 cm FCCL sample is placed on a measuring table, and a four-point probe probe is evenly contacted with the FCCL copper surface to measure the thickness of the copper layer.
[0051] Method for manufacturing flexible copper foil substrate
[0052] First, please refer to Figure 2 , Figure 2 FIG. 1 is a flow chart of manufacturing a flexible copper foil substrate 100 according to an embodiment of the present invention. Figure 2As shown, a method for manufacturing a flexible copper foil substrate according to an embodiment of the present invention comprises: providing a polyimide substrate 1; forming a nickel-copper alloy layer 2 on a first surface 11 of the polyimide substrate 1 by chemical plating; and forming a copper layer 3 on a side of the nickel-copper alloy layer 2 away from the polyimide substrate 1 by electroplating.
[0053] Here, in one embodiment, the nickel-copper alloy layer 2 may be formed simultaneously on the first surface 11 and the second surface 12. In this case, the copper layer 3 is formed on the surfaces of the two nickel-copper alloy layers 2 away from the polyimide substrate 1.
[0054] Next, as for the chemical plating method and the electroplating method, known chemical plating methods and electroplating methods can be used without particular limitation. Specifically, the chemical plating method and electroplating method mentioned above can be used, and will not be described in detail here.
[0055] Example
[0056] Hereinafter, the present invention will be specifically described by referring to each of Examples and Comparative Examples; however, the present invention is not limited to these Examples and Comparative Examples.
[0057] Determination of Corrosion Potential of Nickel-Copper Alloy Layer
[0058] The corrosion potential of the nickel-copper alloy layer can be measured using a potentiostat (model: BioLogic / SP-50e) and a flat plate corrosion test tank (model: ABT-TA-F029) from Northern Lights Technologies.
[0059] First, the polyimide substrate sample plated with a nickel-copper alloy layer was immersed in a 3 vol% sulfuric acid solution for 30 seconds and then washed with water. It was then placed in a flat corrosion test tank as a working electrode for electrochemical testing, wherein the auxiliary electrode was a platinum electrode, the reference electrode was a calomel electrode, and the electrolyte was a 0.02 vol% sulfuric acid solution. After connecting the potentiostat and opening the operating software, the Tafel Plot in the corrosion test mode was selected, the scan rate was set to 300 mV / min, and the scan range was from -0.5V to 0.2V, and the corrosion potential of the nickel-copper alloy layer in a 0.02 vol% sulfuric acid solution was measured.
[0060] Determination of peel strength
[0061] The peel strength between the polyimide substrate and the metal conductive layer in the flexible copper foil substrate was measured using a universal tensile testing machine (model: QC-538M1) from Guanglei Instruments. First, the copper layer thickness of the flexible copper foil substrate was adjusted to 18 μm, and the circuit was made according to the IPC-TM-6502.4.9 specification and the peel strength test at a 90° angle was performed on the universal tensile testing machine.
[0062] In the present invention, peel strength ≥ 0.9 kgf / cm was marked as ○, ≥ 0.7 kgf / cm but less than 0.9 kgf / cm was marked as △, and less than 0.7 kgf / cm was marked as ×.
[0063] Determination of elemental composition of nickel-copper alloy layer
[0064] Using a scanning electron microscope (SEM / EDS) from Jiedong Co., Ltd., the sample of a polyimide substrate coated with a nickel-copper alloy layer was directly placed in the SEM and evacuated without gold coating. The elemental composition of the nickel-copper alloy layer within a range of 200μm*150μm was then analyzed using EDS.
[0065] Plating residue (etching)
[0066] Using a microscope (VK-X3000) from Keyence of Taiwan, China, the etched flexible circuit board sample was placed directly on the analysis platform, and a 50x optical lens was used to observe the thinnest line area (line width / line spacing = 25 / 25μm) to confirm whether there was any metal residue on the shape and outer edge.
[0067] In the present invention, no metal residue is recorded as o, trace metal residue is recorded as △, and obvious metal residue (not completely etched) is recorded as ×. No metal residue is defined as no trace at the edge of the circuit, trace metal residue is defined as the trace width of the circuit edge is less than 2μm, and obvious metal residue is defined as the trace width of the circuit edge is greater than 2μm.
[0068] Circuit adhesion after ENIG
[0069] In the present invention, the adhesion of the circuit after ENIG is determined by visual inspection, and the observation range is the fine circuit area with line width / line spacing = 25 / 25μm. As long as there is any fine circuit area in the entire flexible circuit board that is visible to the naked eye and peeled or turned up, it is defined as poor circuit adhesion and marked as ×; on the contrary, if all the fine circuit areas are complete and well bonded to the polyimide substrate, the circuit adhesion is good and marked as ○.
[0070] Absorbance
[0071] First, a polyimide (PI) substrate coated with a double-sided nickel-copper alloy layer with a total thickness of about 200nm was taken as a sample, immersed in a H2O2 / H2SO4 fast etching solution at room temperature for 20 seconds, taken out, washed with water and dried. Then, a UV-Vis spectrometer was used to analyze the degree of residual coating on the PI substrate, and the absorbance value of the etched sample at a wavelength of 500nm was measured with the PI substrate without coating as the baseline. In addition, the higher the absorbance value, the more residual coating, which means that the nickel-copper alloy layer is less likely to be etched.
[0072] Overall evaluation
[0073] If at least one of the characteristics in Table 1 below is ×, the overall evaluation is ×; if at least one is △, the overall evaluation is △; if all the characteristics are ○ or meet the requirements, the overall evaluation is ○.
[0074] Example 1
[0075] Polyimide substrate pretreatment
[0076] The rolled polyimide substrate (purchased from Damai Technology, model TX6-025) was subjected to continuous hydrophilic modification treatment in a corona treatment machine (purchased from WEDGE, Japan), with the operating conditions of 3 kW power and 3 m / min speed. The hydrophilic treated polyimide substrate was then cut into a size of 20 cm*20 cm and immersed in a 2 wt% KOH solution at 40°C for 150 seconds.
[0077] Chemical nickel-copper alloy layer
[0078] First, referring to the above, the SLP metallization process (SLP process) of Japan Okuno Pharmaceutical Co., Ltd. is used to successively perform charge adjustment, pre-impregnation, catalysis, acceleration and other steps on the hydrophilic polyimide substrate to obtain a polyimide substrate with palladium catalyst on both sides.
[0079] Secondly, a chemical plating solution is prepared in a 5-liter beaker (bath volume is 5L), wherein the chemical plating solution comprises 98.5g nickel sulfate, 7.9g copper sulfate, 106g sodium hypophosphite, 205g sodium citrate and 124g boric acid, and the pH is adjusted to 8.5 with a 50wt% NaOH solution. Next, the polyimide substrate with the palladium catalyst is immersed in the chemical plating solution, reacted at a temperature of 40°C, and the time is controlled to be 2-3 minutes to keep the total thickness of the coating between 200±20μm, and then taken out for washing and drying to form a polyimide substrate with a nickel-copper alloy layer (including a ternary alloy of nickel / copper / phosphorus) plated on both sides.
[0080] Electroplated copper layer
[0081] According to the above method, on the nickel-copper alloy layer of the polyimide substrate plated with the nickel-copper alloy layer, an electroplated copper layer with a copper thickness of about 1 μm on both sides is obtained to serve as a flexible copper foil substrate.
[0082] Line production
[0083] Next, please refer to Figure 3 , Figure 3 The manufacturing process of the flexible circuit board 900 of the present invention is shown. Figure 3As shown, the flexible copper foil substrate 100 obtained in Example 1 is sequentially subjected to known semi-additive processes such as pre-treatment, lamination, exposure, development, copper plating, film stripping, and fast etching to prepare a flexible circuit board 900 with a line width / line spacing of 25 / 25 μm.
[0084] Nickel immersion gold
[0085] Then, if Figure 3 As shown in the figure, after the semi-additive circuit process, the copper circuit of the flexible circuit board is subjected to the well-known nickel immersion gold surface treatment. Specifically, the steps of cleaning, micro-etching, pre-dip, activation, post-dip, nickel immersion, gold immersion and the like are successively carried out using ENIG reagents of Atotech (including ProSelect UC K, MicroEtch C, Aurotech Activator conc., Aurotech FLPlus Post Dip K, AurotechSITPlus, Aurotech SF Plus).
[0086] The specific steps are as follows: 1. Soak the FPC in a 40°C ProSelect UC K solution for 5 minutes to clean the surface, remove it and rinse it with water. 2. Then soak it in a 30°C MicroEtch C solution for 60 seconds to remove the oxide layer on the surface of the copper circuit by microetching, remove it and rinse it with water. 3. Soak it in a 25vol% sulfuric acid solution at 25°C for 3 minutes, remove it and rinse it with water. 4. Soak it in a 25°C Aurotech Activator conc. solution for 1 minute to activate the catalyst, remove it and rinse it with water. 5. Soak it in a 25°C Aurotech FL Plus Post Dip K solution for 3 minutes to remove the catalyst on the polyimide substrate, remove it and rinse it with water. 6. Then soak it in an Aurotech SIT Plus solution at pH = 4.8 and 78°C for 6 minutes to deposit a nickel-phosphorus alloy layer with a thickness of 2-4μm, remove it and rinse it with water. 7. Finally, immerse in Aurotech SF Plus solution containing potassium gold cyanide (purchased from Jialong Technology Engineering Co., Ltd.) as a gold salt at pH = 5.5 and 82°C for 4 minutes to deposit a gold layer with a thickness of 0.04-0.06 μm on the nickel-phosphorus alloy layer (such as Figure 3 The copper circuit board is then surface treated as shown in symbol 4), taken out and washed with water to complete the surface treatment of the copper circuit board of the flexible circuit board.
[0087] Finally, the metal concentration in the chemical plating solution of Example 1, the composition of the nickel-copper alloy layer, and the properties of the nickel-copper alloy layer are summarized in Tables 1 and 2. The determination methods of each property are described above and will not be repeated here.
[0088] Comparative Example 1
[0089] The polyimide substrate with palladium catalyst on both sides was immersed in SLP-660 plating solution (purchased from Okuno Pharmaceutical Co., Ltd.), reacted at a temperature of 36°C for 2 minutes and 30 seconds, taken out, washed and dried, to form a polyimide substrate with nickel / phosphorus alloy plated on both sides with a total thickness of about 200 μm.
[0090] Thereafter, the copper layer was electroplated, the circuit was fabricated, and nickel immersion gold was applied in the same manner as in Example 1, thereby obtaining the flexible copper foil substrate and flexible circuit board of Comparative Example 1.
[0091] Comparative Example 2-6 and Example 2-6
[0092] Next, in the same manner as in Example 1, the metal concentrations of Ni and Cu in the chemical plating solution (i.e., the amount of nickel sulfate and the amount of copper sulfate) and the composition of the nickel-copper alloy layer were changed based on the following Table 1, thereby obtaining the flexible copper foil substrates and flexible circuit boards of Comparative Examples 2-6 and Example 2-6. In addition, the metal concentrations in the chemical plating solution of Comparative Examples 2-6 and Example 2-6, the composition of the nickel-copper alloy layer, and the characteristics of the nickel-copper alloy layer are summarized in Tables 1 and 2.
[0093]
[0094] Table 2
[0095]
[0096] First, it can be seen from Table 1 that because Examples 1-7 all use chemical plating to form the nickel-copper alloy layer, and the copper content in the nickel-copper alloy layer is greater than 30wt% and the phosphorus content is less than 5wt%, the corrosion potential of the nickel-copper alloy layer in a 0.02vol% sulfuric acid solution can be greater than -20mV, and it has the effect of resisting electrochemical corrosion.
[0097] Next, because the copper content in the nickel-copper alloy layer of Comparative Examples 1-5 is less than 30wt%, the corrosion potential of the nickel-copper alloy layer produced by the comparative examples is less than -20mV, which does not meet the requirements. In addition, because the phosphorus content in the nickel-copper alloy layer of Comparative Examples 2-5 is greater than 5wt%, metal residues remain during etching, resulting in incomplete etching.
[0098] Specifically, please refer to Figure 4 , Figure 4 (a) is a photograph of the appearance of the etched circuit of Comparative Example 5; Figure 4 (b) is a photograph of the appearance of the etching circuit of Example 1. Figure 4 As shown in (a), in Comparative Example 5, metal remains after etching, resulting in incomplete etching, which does not meet the requirements; in contrast, Figure 4As shown in (b), in Example 1, only a trace amount of metal remains after etching, which meets the requirements.
[0099] Furthermore, because the copper content in the nickel-copper alloy layer of Comparative Examples 1-3 is very low, and the nickel-copper alloy layer of Comparative Example 1-2 does not even contain copper, the corrosion potential of this comparative example is very small (less than -70mV), and there is a situation of circuit peeling after ENIG, and the circuit adhesion is poor, which does not meet the requirements.
[0100] Specifically, please refer to Figure 5 , Figure 5 (a) is a photograph of Comparative Example 1 after ENIG; Figure 5 (b) is a photo of Example 1 after ENIG. Figure 5 As shown in the circled area of (a), the circuit peeling occurred in Comparative Example 1 after ENIG, and the circuit adhesion was poor, which did not meet the requirements; in contrast, Figure 5 As shown in the circled portion of (b), the circuit of Example 1 is still good after ENIG, meeting the requirements.
[0101] Next, in Example 1, the etching property and overall evaluation were △ because a trace amount of metal remained. In Example 6, although the corrosion potential of -11.6 mV was achieved, the peel strength was 0.868 kgf / cm, slightly less than the standard value of 0.9 kgf / cm, so the peel strength and overall evaluation were △.
[0102] In addition, in Comparative Example 6, although the etching property, corrosion potential and circuit adhesion are all ○ or meet the requirements, because the copper content in the nickel-copper alloy layer is greater than 80wt%, the peel strength is significantly reduced to only 0.654kgf / cm, so the peel strength and overall evaluation are ×.
[0103] Then, from Table 2 and Figure 6 The relationship between the absorbance and the appearance of the sample after etching can be known. Figure 6 (a) is a photo of the sample after etching of Example 4 of the present invention; Figure 6 (b) is a photo of the sample after etching of Example 1 of the present invention; Figure 6 (c) is a photograph of the sample after etching of Comparative Example 5 of the present invention.
[0104] First, as shown in Table 2 and Figure 6 As shown in (a), the absorbance value of Example 4 is 0.273, and the nickel-copper alloy layer is etched cleanly. The sample has a lighter color and is closer to the appearance of the PI substrate, which meets the requirements. Figure 6 As shown in (b), the absorbance value of Example 1 is 0.463, and there is a trace amount of residual nickel-copper alloy layer. The sample has a darker appearance than Example 4, which still meets the requirements. On the other hand, as shown in Table 2 and Figure 6As shown in (c), the absorbance value of Comparative Example 5 is 0.730, and the nickel-copper alloy layer thereof has a lot of residues and is not etched cleanly. The sample has an appearance that is darker than Example 1, which does not meet the requirements.
[0105] The present invention utilizes a chemical plating method and a specific composition of a nickel-copper alloy layer to improve the corrosion potential of the nickel-copper alloy layer in a sulfuric acid solution, and to obtain a flexible copper foil substrate that is resistant to electrochemical corrosion and has sufficient peeling strength.
[0106] The present invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining technical means disclosed in different embodiments are also included in the technical scope of the present invention.
Claims
1. A flexible copper foil substrate, characterized in that: Include: Polyimide substrate; A nickel-copper alloy layer formed on at least one side of the polyimide substrate by chemical plating, wherein the nickel-copper alloy layer comprises nickel, copper and phosphorus, wherein the content of the copper is greater than 30wt% of the nickel-copper alloy layer, the content of the phosphorus is less than 5wt% of the nickel-copper alloy layer, and the corrosion potential of the nickel-copper alloy layer in a 0.02vol% sulfuric acid solution is greater than -20mV; and The copper layer is formed on the side of the nickel-copper alloy layer away from the polyimide substrate and is combined with the nickel-copper alloy layer to form a metal conductive layer.
2. The flexible copper foil substrate according to claim 1, characterized in that The copper content is less than 80 wt % of the nickel-copper alloy layer.
3. The flexible copper foil substrate according to claim 1, characterized in that The nickel-copper alloy layer is a single plating layer.
4. The flexible copper foil substrate according to claim 1, characterized in that The nickel-copper alloy layer further includes at least one selected from the group consisting of iron, cobalt, molybdenum, tungsten, tin, chromium and zinc.
5. The flexible copper foil substrate according to any one of claims 1 to 4, characterized in that: The copper layer is formed on the nickel-copper alloy layer by electroplating, and the thickness of the copper layer is 0.2-20 μm.
6. The flexible copper foil substrate according to any one of claims 1 to 4, characterized in that: The peel strength between the metal conductive layer and the polyimide substrate is greater than or equal to 0.7 kgf / cm.
7. The flexible copper foil substrate according to claim 5, characterized in that: The peel strength between the metal conductive layer and the polyimide substrate is greater than or equal to 0.7 kgf / cm.